THE EFFECTIVENESS OF THE EXCLUSIVE BREAST MILK (ASI) FEEDING PROGRAM IN BONTOBANGUN VILLAGE, BULUKUMBA REGENCY - Yadi, Harfina; Guntur, Muhammad; Halim, Didin (Jurnal Aktor, 2025)
This research aims to determine the effectiveness of the exclusive breast milk (ASI) service program in Bontobangun Village, Bulukumba Regency.This research includes qualitative descriptive research with data collection techniques including observation, interviews and documentation. Data analysis techniques consist of data collection, data condensation, data presentation, and drawing conclusions. The results of the research show that the effectiveness of the Exclusive Breast Milk (ASI) Program Services in Bontobangun Village, Bulukumba Regency including the dimension of achieving goals has been effective, the community has responded positively to the existence of this program and the IMD figures are increasing every year. The integration dimension shows that it is not yet effective because there are still some mothers who do not give their babies the right to breast milk, while the adaptation dimension is still not effective because in terms of increasing capacity, existing resources are not maximal in utilizing social media for socialization and the community wants it to exist. a wider, closed space for mothers.